Effect of Heteroatoms on Field-Induced Slow Magnetic Relaxation of Mononuclear Feiii (S = 5/2) Ions Within Polyoxometalates - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2018)
In this paper, the synthesis and magnetic properties of mononuclear FeIII-containing polyoxometalates (POMs) with different types of heteroatoms, TBA7H10[(A-α-XW9O34)2Fe] (IIX, X = Ge, Si; TBA = tetra-n-butylammonium), are reported. In these POMs, mononuclear highly distorted six-coordinate octahedral [FeO6]9- units are sandwiched by two trivacant lacunary units [A-α-XW9O34]10- (X = Ge, Si). These POMs exhibit field-induced slow magnetic relaxation based on the single high-spin FeIII magnetic center (S = 5/2). Combining experiment and ab initio calculations, we investigated the effect of heteroatoms of the lacunary units on the field-induced slow magnetic relaxation of these POMs. By changing the heteroatoms from Si (IISi) to Ge (IIGe), the coordination geometry around the FeIII ion is mildly changed. Concretely, the axial Fe-O bond length in IIGe is shortened compared with that in IISi, and consequently the distortion of the [FeO6]9- unit in IIGe from the ideal octahedral coordination geometry becomes larger than that in IISi. The effective demagnetization barrier of IIGe (11.4 K) is slightly larger than that of IISi (9.2 K). Multireference ab initio calculations predict zero-field splitting parameters in good agreement with experiment. Although the differences in the coordination geometries and magnetic properties of IIGe and IISi are quite small, ab initio calculations indicate subtle changes in the magnetic anisotropy which are in line with the observed magnetic relaxation properties. © 2018 American Chemical Society.